Biocompatible Scaffolds for Human-Induced Pluripotent Stem Cell Transplantation and Modeling Post-Stroke Recovery in Three-Dimensional Neural Cell Culture - Huynh, Joann; B. Jensen, Matthew; Jager, Lindsey (Journal of Evolving Stem Cell Research, 2016)
Human-induced pluripotent stem cells (HiPSCs) demonstrate promise in their ability to differentiate into neural cells and ultimately replace the cell types and thereby brain tissue damaged by stroke. This may diminish cognitive impairment due to stroke. Prior to transplantation, an appropriate scaffold must be determined to allow for heightened accuracy by facilitating proper adhesion, differentiation, and proliferation, increasing the likelihood of success, as will be defined in this review, in vivo. This paper aims to provide a review of available biocompatible scaffolds and their efficacy, to provide insight for future research utilizing clinical trials to study stem cell therapy as a form of post-stroke recovery. A systematic review of scaffolds outlined in full-text, peer-reviewed articles with unique experimental data, available on PubMed, will be conducted to determine an ideal scaffold, based on article and scaffold selection criteria best suited for the transplantation of human-induced pluripotent stem cells.
Keywords: Biocompatible; scaffold; stem cell; stroke; three-dimensional neural cell culture